Diagnostic validity and clinical utility of genetic testing for hypertrophic cardiomyopathy: a systematic review and meta-analysis. Issue 1 (6th April 2022) - Christian, Susan; Cirino, Allison; Hansen, Brittany; Harris, Stephanie; Murad, Andrea M; Natoli, Jaime L; Malinowski, Jennifer; Kelly, Melissa A
Abstract : Objective: This study summarises the diagnostic validity and clinical utility of genetic testing for patients with hypertrophic cardiomyopathy (HCM) and their at-risk relatives. Methods: A systematic search was performed in PubMed (MEDLINE), Embase, CINAHL and Cochrane Central Library databases from inception through 2 March 2020. Subgroup and sensitivity analyses were prespecified for individual sarcomere genes, presence/absence of pathogenic variants, paediatric and adult cohorts, family history, inclusion of probands, and variant classification method. Study quality was assessed using the Newcastle-Ottawa tool. Results: A total of 132 articles met inclusion criteria. The detection rate based on pathogenic and likely pathogenic variants was significantly higher in paediatric cohorts compared with adults (56% vs 42%; p=0.01) and in adults with a family history compared with sporadic cases (59% vs 33%; p=0.005). When studies applied current, improved, variant interpretation standards, the adult detection rate significantly decreased from 42% to 33% (p=0.0001) because less variants met criteria to be considered pathogenic. The mean difference in age-of-onset in adults was significantly earlier for genotype-positive versus genotype-negative cohorts (8.3 years; p<0.0001), MYH7 versus MYBPC3 cohorts (8.2 years; p<0.0001) and individuals with multiple versus single variants (7.0 years; p<0.0002). Overall, disease penetrance in adult cohorts was 62%, but differed significantly depending on if probands were included or excluded (73% vs 55%; p=0.003). Conclusions: This systematic review and meta-analysis is the first, to our knowledge, to collectively quantify historical understandings of detection rate, genotype-phenotype associations and disease penetrance for HCM, while providing the answers to important routine clinical questions and highlighting key areas for future study.